Attitudes of ambulatory care older Nepalese patients towards deprescribing and predictors of their willingness to deprescribe - Shakti Shrestha; Roshan Giri; Hari Prasad Sapkota; Siddhartha Sharma Danai; Ahsan Saleem; Shreeshab Devkota; Sagar Shrestha; Bhojraj Adhikari; Arjun Poudel (SAGE Publishing, 2021)
Introduction: Older adults continue to receive potentially inappropriate medications necessitating the need for medication optimization, by deprescribing. To ensure a holistic approach to deprescribing, it is essential to understand the perception of older adults towards deprescribing. This study aimed to assess the attitude of older ambulatory patients towards deprescribing and to identify factors predicting their willingness to deprescribe. Methods: A cross-sectional survey was conducted in central Nepal between March and September 2019 among 385 older ambulatory care patients (aged ⩾65 years) who were taking at least one regular medicine. The perception of patients towards deprescribing was assessed using the revised Patients' Attitudes Towards Deprescribing (rPATD) questionnaire via a face-to-face interview method. Descriptive statistics were performed to describe patients' characteristics and their attitudes towards deprescribing. A multivariate logistic regression analysis was used to determine predictors of the willingness of older ambulatory patients towards deprescribing. Results: The median [interquartile range (IQR)] age of patients was 72 (8) years. Nearly three in five patients (64.9%) had hypertension, with 11.2% having polypharmacy. More than half of the patients (57.4%) would be willing to stop one or more of their regular medicines if their doctor said it was possible to do so. Regression analysis showed that age [odds ratio (OR) 0.946; 95% CI 0.913, 0.981; p  = 0.003] and concerns about stopping medicine score (OR 0.541; 95% CI 0.334, 0.876; p  = 0.013) were predictors of the willingness of the older patients towards deprescribing. Conclusion: One in two older ambulatory care patients in Nepal would be willing to have one or more of their medicines deprescribed. The factors predicting their willingness to deprescribe are their age and concerns about stopping medicines. Clinicians should consider discussing the possibility of deprescribing with older patients for the prevention of potential medication-related harms. Plain Language Summary What do older Nepalese patients think about withdrawal or dose reduction of an inappropriate medication? Introduction: Research suggests that older adults (aged ⩾65 years) continue to receive medications that have the potential for harm rather than a benefit. This necessitates the need for withdrawal or dose reduction of such inappropriate medications, the process known as deprescribing. Understanding what older patients think about this process could be a stepping-stone to the general approach for its implementation. Data on deprescribing is lacking from Nepal. Therefore, we designed a survey to explore the attitude of older patients towards deprescribing and factors that could predict their willingness to deprescribe. Methods: This study was conducted between March to September 2019 among 385 older patients who were taking at least one regular medicine and were visiting selected hospitals of Nepal for outpatient services. We performed a face-to-face interview to assess the attitude of patients towards deprescribing using a validated tool called revised Patients' Attitudes Towards Deprescribing (rPATD) questionnaire that quantified the response through scoring. The data were subjected to statistical analysis to determine the attitudes of Nepalese older patients towards deprescribing and to develop a model to predict their willingness to deprescribe. Results: The average age of the participant was 72 years with 65% having hypertension and 11% using more than five medications. Our data suggested that one in two older Nepalese patients would be willing to stop one or more of their regular medications if their doctors said it was possible to do so. Their willingness to deprescribe could be predicted from their age and concerns about stopping medications. Conclusion: Clinicians should consider discussing the possibility of deprescribing with older patients for the prevention of potential medication-related harms.